Analysis of Food Ordering Information Systems and Web-Based Digital Payments for Cafes - Jatmikho, Shendra; Riki (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
Cafe is a place of business engaged in culinary. Currently, the café is a place that is quite in demand by all circles, because it can be used as a place to relax or do assignments for students. However, many cafes have difficulty in serving reservations and still use conventional systems. With a menu ordering information system and web-based digital payments applied to this café, it aims to speed up the menu ordering process, facilitate payments with digital wallets and make the ordering process more efficient. With this information system, café sales report data becomes computerized, so that data can be stored properly. The method used in this study uses data collection methods, namely by observation, interviews, and literature studies. As for system development using a methodology or prototype approach. Based on the research conducted, it produced a menu ordering information system and web-based digital payments using PHP and Mysql. And from testing the system with blackbox testing conducted by 2 testers, the system made was able to make the ordering process at the café more efficient.